2018
DOI: 10.1080/19460171.2018.1534132
|View full text |Cite
|
Sign up to set email alerts
|

From exemplary practitioners to urban chameleons? The role of the citizen in the redistribution of tasks in local governance

Abstract: This article further theorizes exemplary practitioners' roles in neighborhood governance by building on the framework of the four ideal types of practitioners-frontline worker, everyday fixer, social entrepreneur and boundary spanner. An actor-focused approach was applied which delivered data to reconstruct processes in which a single citizen practitioner engaged in an Amsterdam neighborhood. Data were collected through shadowing and interviewing him for 2 months. It is shown how this exemplary practitioner co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Seven studies drew on surveys and two on focus groups. The studies included a wide range in sample size, from an in-depth ethnographic study of one practitioner (Kovács, 2020), to interviews of over 200 participants (Lindsay et al, 2021), to a survey with 385 participants (McCuaig et al, 2019). The median sample size across the studies is 37.5 (excluding non-empirical papers).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies drew on surveys and two on focus groups. The studies included a wide range in sample size, from an in-depth ethnographic study of one practitioner (Kovács, 2020), to interviews of over 200 participants (Lindsay et al, 2021), to a survey with 385 participants (McCuaig et al, 2019). The median sample size across the studies is 37.5 (excluding non-empirical papers).…”
Section: Resultsmentioning
confidence: 99%
“…Nissen (2010, p. 379), examining successful youth work professionals, reported that: “Their ability to adapt to local circumstances allowed them to gain power and access across diverse groups. Failure to do this risked alienating one of these groups, impeding progress toward the vision.” Similarly, Kovács (2020, p. 140) pointed to effective boundary spanners’ “extensive knowledge of local conditions and ‘holistic problem orientation’, which allows them to prioritize the complex and interrelated neighbourhood problems.” Further, in a boundary-spanning role aimed at addressing labor market inclusion, Lindsay et al (2021, p. 932) emphasize the importance of “deep community knowledge.” This seems to refer to an in-depth understanding of the various issues and concerns at play in a community as well as to its sources of strength.…”
Section: Resultsmentioning
confidence: 99%
“…In exhibiting the multiple behaviors of transformational leadership (Podsakoff et al 1990), the ECBO leaders of this study engage in a type of role switching dynamic (Kovács 2020). That is, these effective leaders, due to both necessity and devotion, find themselves moving across diverse responsibilities ranging from the most commonplace, such as showing someone how to use a public bus system, to establishing a long-term community vision.…”
Section: Key Findingsmentioning
confidence: 99%